Glutamate-stimulated protein phosphorylation in cultured hippocampal pyramidal neurons - Scholz, WK (J Neurosci, 1991)
The regulation of second-messenger production and protein phosphorylation by glutamate has been investigated in primary cultures of pure hippocampal pyramidal neurons. Embryonic rat pyramidal neurons were prepared according to the procedures of Bartlett and Banker (1984) and studied 1–21 d after plating. Glutamate caused a transient increase in intracellular free [Ca2+], determined with fura-2, in the presence of 1.26 mM extracellular Ca2+, but not in 50 nM free Ca(2+)-containing solution. Glutamate also transiently increased cellular diacylglycerol content in both normal and low-[Ca2+] media. Neurons were prelabeled with 32P-orthophosphate to label intracellular ATP, then stimulated with glutamate (100 microM). A rapid transient incorporation of 32P into primarily three proteins of 120, 87, and 48 kDa was found by analysis of two-dimensional gels. At 30 sec after glutamate stimulation, 32P incorporation into the 87-kDa and 48-kDa proteins peaked (240% and 170% basal levels, respectively), and by 2 min, phosphorylation of the 87-kDa protein had returned to basal levels, while that of the 48-kDa protein decreased but remained above control levels. The phosphorylation of these proteins appeared to be mediated by protein kinase C (PKC) because all three showed an increase in phosphorylation after phorbol ester treatment of cultures. Phosphate incorporation was accompanied by an acidic shift in the isoelectric point of both 87- and 48-kDa proteins. Glutamate stimulation resulted in phosphorylation in the presence and absence of Ca2+ influx. Antibody recognition and biochemical characteristics indicated that the 87-kDa phosphoprotein is the PKC substrate MARCKS (myristoylated, alanine-rich C-kinase substrate). The 48-kDa protein, though very similar to GAP-43, was not recognized by specific antibodies raised against GAP-43. These results suggest that glutamate stimulates the transient generation of second messengers that activate PKC in hippocampal neurons, resulting in a significant increase in the phosphorylation of three specific proteins.